Sentimentos de professores e de alunos de duas escolas públicas de tempo integral no Estado de São Paulo - Necyk, Márcia Teresa Campos (2012)
This research s objective is to understand how the emotional dimension manifests itself in schools where children stay full time, by investigating feelings and their inducing situations. For this, we made observations in school classes of two public institutions that participate in the Full-Time School Project of the State of São Paulo. Identifying teacher s and student s feelings has proved to be a valuable instrument, since it has made possible reveal the research participant s needs in relation to the school environment and to the learning-teaching process. Given that the emotional dimension has been prioritized, the chosen theoretical reference was the development theory of Henri Wallon. In teachers we have identified feelings such as: pride for their profession, trust and respect for the students and contradictory feelings towards the school, like satisfaction/frustration and happiness/discouragement. Students revealed situations in which they feel interested and those that make them feel unmotivated. As result of the investigation, we have perceived a significant gap between what had been proposed by the Project s Curricular Policy and what is actually experienced in the schools. Interviews and observations suggest the need for changes in the Project, like: upgrading of school installations, teachers continuous learning, teachers exclusive dedication to the school, improvement in meals, teacher-student relationship enhancement, incentive to working in group, carrying out activities that promote the development of all human dimensions and basic curriculum activities integration with workshops. We have also found that, in spite of the present difficulties, the interviewed teachers keep hopeful that the Project will be improved and are looking forward to full-time schools being able to effectively provide a high quality education to the participant children